Effects of Therapeutic Exercise Intensity on Cerebral Palsy Outcomes: A Systematic Review With Meta-Regression of Randomized Clinical Trials - Hsu, Che-Wei; Kang, Yi-No; Tseng, Sung-Hui (Frontiers in Neurology, 2019)
Background and Objective: Intensive physical therapy or exercise has been associated with favorable cerebral palsy (CP) outcomes, but few studies have investigated the effects of exercise intensity on the improvement in CP outcomes. In this study, we assessed the effects of intensive exercise-based therapy on improvement in gross motor function in children with CP. Methods: We searched three databases for randomized clinical trials evaluating the effects of therapeutic exercise training by using Gross Motor Function Measurement (GMFM) 66 and 88 among children with CP. Studies that used interventions in addition to therapeutic exercise were excluded from the present meta-analysis. Exercise intensity was defined using the number of training hours per day and duration of intervention (in weeks). The effects of the number of daily training hours and program duration on GMFM improvement were evaluated using meta-regression. Results: The comprehensive search returned 270 references, and 13 of 270 references met our eligibility criteria. The 13 trials recruited 412 children with CP. These trials measured motor improvements by using GMFM-66 (n = 8) and GMFM-88 (n = 5). The GMFM scores in the children who received the therapeutic intervention did not show significantly greater improvement than those of the children who received standard care. Meta-regression analysis revealed that the improvement in GMFM scores was positively associated with the number of daily training hours (point estimate = 0.549; p = .031) and program duration (point estimate = 0.067; p = .075). Discussion and Conclusions: Intensive physical exercise improved CP outcomes in the intervention and standard therapy groups. The duration of therapeutic intervention improved CP outcomes among the children who received the therapeutic intervention, while an increase in the number of daily training hours improved in CP outcomes in the children who received standard therapy.